Experiencing, anticipating, and witnessing discrimination during the COVID-19 pandemic: Implications for health and wellbeing among Asian Americans - Dhanani, Lindsay Y.; Franz, Berkeley; Pham, Carolyn T. (Frontiers in Public Health, 2022)
The onset of the COVID-19 pandemic spurred increased racial animus toward Asians and Asian Americans (A/AA) who have since been contending with increased racism and violence. While some of the harm associated with this increased prejudice may derive from personally experienced discrimination, the COVID-19 pandemic has also been marked by an increase in vicarious exposure to discrimination as well as increased anticipation of discrimination, both of which may be taxing for the mental and physical health of A/AA. The goal of this study, accordingly, was to examine the effects of personal experiences of discrimination, vicarious exposure to discrimination, and anticipated discrimination on depressive symptoms, physical health symptoms, sleep quality, and sleep disturbances among A/AA. Results from our two-wave field survey demonstrated that experiencing and anticipating discrimination were associated with mental and physical health symptoms as well as sleep disturbances. Further, personal experiences of discrimination interacted with vicarious discrimination to determine physical health symptoms such that greater vicarious exposure weakened the relationship between experienced discrimination and physical health symptoms. These findings demonstrate the need to mobilize resources to combat the multipronged, negative implications of the recent rise in anti-Asian prejudice during the COVID-19 pandemic.